Can immunization with Bacillus Calmette-Guérin (BCG) protect against Alzheimer's disease?. (February 2019) - Gofrit, Ofer N.; Bercovier, Herve; Klein, Benjamin Y.; Cohen, Irun R.; Ben-Hur, Tamir; Greenblatt, Charles L.
Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder which is the most prevalent cause of dementia in the western world. Currently, it is the most expensive disease in America, costing more than heart diseases and cancer and as the world population is getting older it is expected to become the most expensive medical disorder in the world. AD is characterized by three core pathologies: accumulation of amyloid β (Aβ) plaques, neurofibrillary tangles (NFT) and sustained inflammation. It is now believed that inflammation provides the link between Aβ and NFT. The immune system is therefore, a major player in the pathogenesis of AD. Here we propose that Bacillus Calmette-Guérin (BCG) could affect the incidence of AD. Bacillus Calmette-Guérin (BCG) is a live attenuated Mycobacterium bovis preparation first developed as a vaccine against M. tuberculosis . It has been shown to be moderately effective in preventing tuberculosis, while noted to induce modifications in inflammatory response and to regulate the immune system. Intra-vesical administration of BCG is used successfully in the past four decades to prevent recurrence of non-muscle invasive bladder cancer. In this manuscript we investigate the hypothesis that exposure to BCG decreases the prevalence of AD in elderly population and that this occurs through modulation of the immune system. Our hypothesis is based on several lines of evidence: lower prevalence of AD in countries with high BCG coverage, ability of BCG to ameliorate several conditions involving the immune system like type 1 diabetes mellitus and multiple sclerosis, animal models of AD in which BCG shows therapeutic potential and a plausible molecular mechanism which may be the basis for this hypothesis. Namely, elevated systemic levels of IL-2 (as found when BCG is given intra-vesically) that amplify Treg cells that inhibit AD associated inflammation, decreased plaque formation and restore cognitive function. To test this hypothesis one may study cognition in the large available "natural adult population" exposed to high dose of BCG through the bladder. Bladder cancer survivors not given BCG can serve as control group. This population can be used without adding any medical intervention.